Home-Based Practical Parents Involvement in Assisting Children Learn English - Ratna Rintaningrum; Choirul Mahfud; Umi Trisyanti; Moh. Saifulloh; Banu Prasetyo (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2022)
Increasingly, English is becoming a popular language for young learners. In order to support the learning of English at early age, the involvement of parents is highly important. It is because schools are not the only determinant for success, but parents also have a very huge responsibility to their children education. Nowadays, the role of parents in education in general, and in the learning of English in particular is being questioned. The aim of the study is to analyse home-based parental involvement in assisting their children learn English. A face to face interview was conducted to parents with different gender, level of education, and professions. There are about 6 participants involved in the study. The study shows that parents with different professions provide a variety of ways on how they help their children learn English at home. Educational background and professions of the parents play an important role on how parents provide assistances to their children. Parents with higher level of education are more likely to provide more systematically and more various assistance to their children. The study is expected to encourage schools and parents to work more collaboratively in improving their children with better performance.